In-plane topological p-n junction in the three-dimensional topological insulator Bi(2−x)Sb(x)Te(3−y)Se(y) - Tu, Ngoc Han (Nat Commun, 2016)
A topological p-n junction (TPNJ) is an important concept to control spin and charge transport on a surface of three-dimensional topological insulators (3D-TIs). Here we report successful fabrication of such TPNJ on a surface of 3D-TI Bi(2−x)Sb(x)Te(3−y)Se(y) thin films and experimental observation of the electrical transport. By tuning the chemical potential of n-type topological Dirac surface of Bi(2−x)Sb(x)Te(3−y)Se(y) on its top half by using tetrafluoro-7,7,8,8-tetracyanoquinodimethane as an organic acceptor molecule, a half surface can be converted to p-type with leaving the other half side as the opposite n-type, and consequently TPNJ can be created. By sweeping the back-gate voltage in the field effect transistor structure, the TPNJ was controlled both on the bottom and the top surfaces. A dramatic change in electrical transport observed at the TPNJ on 3D-TI thin films promises novel spin and charge transport of 3D-TIs for future spintronics.